Experimental Study of Steady Blowing from the Trailing Edge of an Open Cavity Flow - Naser Al Haddabi; Konstantinos Kontis; Hossein Zare-Behtash (Aerospace)
Cavity flows have a wide range of low-speed applications (<semantics>M≤0.3</semantics>), such as aircraft wheel wells, ground transportations, and pipelines. They induce strong flow oscillations which can substantially increase noise, drag, vibration, and lead to structural fatigue. In the current study, a steady jet was forced from the cavity trailing edge with different momentum fluxes (J = 0.11 kg/m·s2, 0.44 kg/m·s2, and 0.96 kg/m·s2). The aim of this study was to investigate the impact of the steady jet on the time-averaged flow field and the cavity separated shear layer oscillations for an open cavity with a length-to-depth ratio of <semantics>L/D=4</semantics> at <semantics>Reθ=1.28×103</semantics>. Particle image velocimetry, surface oil flow visualisation, constant temperature anemometry, and pressure measurements were performed. The study found that increasing the jet momentum flux caused a significant increase in thickness and deflection of the cavity separated shear layer. Due to the counterflow interaction between the jet and cavity separated shear layer, the growth rate (<semantics>dδω/dx</semantics>) of the cavity separated shear layer increased significantly from 0.193 for the no-jet case to 0.273 for the J = 0.96 kg/m·s2 case. As a result, the return flow rate increased, causing the separation point on the cavity floor to shift upstream from <semantics>x/L≈0.2</semantics> for the no-jet case to <semantics>x/L≈0.1</semantics> for the J = 0.96 kg/m·s2 case. Furthermore, increasing the jet momentum flux increased the broadband level of the cavity separated shear layer oscillations.